Development of obstacle avoidance technique for multi agent autonomous surface vessel using optimal reciprocal collision avoidance - Muhammad Irsyad bin Sahalan (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The development of field robotic, including autonomous surface vessel (ASV) is progressing toward swarming agents operation. It is essential that swarming ASVs to acquire collision avoidance (CA) capability as they are moving together within a confined space. Optimal Reciprocal Collision Avoidance (ORCA) is one of the prominent collision avoidance technique based on Velocity Obstacle (VO) principle for swarming agents application. However, the issue is most predecessors implement ORCA on holonomic agent while ASV is a non-holonomic agents. In addition implementation of ORCA to ASV has to consider the mechanics of a boat, such as back position rudder and no brakes. Along with that, the water surface environment such as wave and maritime traffic system, COLREGS are also factors to consider. Therefore, this research verifies whether ORCA technique is applicable for implementation on ASVs system and measuring the success performance of collision avoidance. The main objective of this research is to develop a swarm collision avoidance technique for ASVs based on ORCA computation as well as observing the differences performance of the technique as the ASVs simulation scenarios are manipulated. In order to achieve the objectives, it takes the measure of designing the swarming ASVs architecture as to comply with ORCA implementation. Furthermore, ASVs model was analysed in kinematic modelling and control system block diagram to identify its motion behaviour. Thus the model was built into simulation tests to implement swarming ASVs' with ORCA collision avoidance technique. As results, ORCA implementation had successful avoid collision in default two and four agents scenario. Changing the communication range directly affects the feasibility of ORCA while other parameters, such as speed and update rate may do so at certain combination. Wave effect is still tolerable for the ASVs' capability as long as it is below the force 98-140N and 6Hz frequency of the simulation tests. Within selected wave parameter tests, 70-98N and 1Hz, the ASVs were recorded to have 30% chance of collision and 97.5-100% of mission success.